Spinel / layered composite phase modified lithium-rich manganese-based positive electrode material and preparation method thereof

By introducing spinel phase into lithium-rich manganese-based positive electrode material to form spinel/layered composite phase, the problem of voltage and energy storage density decay during the cycle is solved, and the electronic conductivity and current carrying capacity of the material are significantly improved. Sub-mobility achieves higher cyclic stability and electrochemical properties.

CN119153643APending Publication Date: 2024-12-17XIAN TECH UNIV

Patent Information

Application Number
CN202411071826.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-06
Publication Date
2024-12-17

AI Technical Summary

Technical Problem

The existing lithium-rich manganese-based positive electrode materials have problems such as fast voltage attenuation, decay of energy storage density and poor rate performance during the cycle process. The existing modification methods cannot effectively improve their cycle stability and electrochemical performance.

Method used

By introducing spinel phase into lithium-rich manganese-based positive electrode material, spray pyrolysis and sintering process are used to regulate the transition metal cation ratio to form spinel/layered composite phase, and improve electron conductivity and carrier mobility , form a three-dimensional ion diffusion channel to improve the conductivity and cyclic stability of the material.

Benefits of technology

It significantly suppresses the decline of median voltage and energy storage density, improves the transmission speed of lithium ions and the ionic conductivity of the material, extends the cyclic stability and electrochemical performance of the material, and improves the overall performance of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119153643A_ABST
    Figure CN119153643A_ABST
Patent Text Reader

Abstract

The invention relates to a spinel / layered composite phase modified lithium-rich manganese-based positive electrode material and a preparation method thereof. The preparation method comprises the following steps: adding lithium acetate, manganese acetate, cobalt acetate and nickel acetate into deionized water, and proportioning according to a general formula LiNixCoyMnzO2 * Li2MnO3 (x + y + z = 1, 0.5 < = xlt, 0.75, 0.2 < = ylt, 0.25, 0 < = z < = 0.3) to obtain a salt solution; precursor powder is prepared through a spray pyrolysis method; carrying out high-temperature calcination treatment on the precursor powder to obtain powder; adding conductive active carbon into the powder, and carrying out ball milling in absolute ethyl alcohol; and drying the ball-milled material in a blast drying oven, and standing to obtain spinel / layered composite phase modified lithium-rich manganese-based positive electrode material powder. The charge transport characteristic and the dynamic performance of the lithium-rich manganese-based positive electrode material are improved, so that the median voltage of the positive electrode material is greatly improved to 3.78 V, and meanwhile, the overall stability of the positive electrode material is greatly improved. The finally prepared button cell shows excellent cycling stability, and within the voltage of 2-4.8 V, the average median voltage decline of each cycle is 1.15 mV after 400 cycles of 1C current; and meanwhile, the synthesis steps are simple and convenient, and the lithium-rich manganese-based positive electrode material can be prepared by adopting conventional equipment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of battery positive electrode materials, and in particular to a spinel / layered composite phase modified lithium-rich manganese-based positive electrode material and a preparation method thereof. Background Art

[0002] Compared with other cathode materials, lithium-rich manganese-based cathode materials show significantly high discharge capacity, high mass specific energy storage density and high working voltage. It has received extensive attention and has become one of the most promising cathodes for the next generation of lithium-ion batteries. However, due to the existence of anion redox processes, oxygen will inevitably be released during the charge and discharge process, which will cause a series of problems. Specifically, the application of lithium-rich manganese-based cathode materials in lithium-ion batteries mainly has three problems: fast voltage decay (structural changes, transition metal dissolution, and side reactions between active substances and electrolytes during the cycle will lead to capacity decay), low first coulomb efficiency (in the process of Li2MnO3 activation, Li2O is net released, and oxygen precipitation is an irreversible process, which will cause irreversible changes in the material structure, making the released lithium ions unable to be embedded in the subsequent discharge process), capacity decay during the cycle, and poor rate performance (low electronic conductivity and ionic conductivity, which is also related to the migration of transition metals to the lithium layer to block the lithium ion diffusion channel). This directly affects its practical application. The method for modifying the structure of the complex phase is simple, controllable and easy to repeat. It also significantly improves material performance and is one of the commonly used methods to improve the structural stability and electrochemical performance of lithium-rich manganese-based positive electrode materials. The overall cycle stability of lithium-rich manganese-based positive electrode materials can be improved through different complex phase structure modifications.

[0003] Most of the existing modification methods are co-precipitation methods to prepare lithium-rich manganese-based positive electrode materials. Among them, the patent with application number "CN201911099470.7" discloses a method for preparing a layered-spinel composite phase positive electrode material, which can improve the rate performance and thermal stability of the lithium-rich manganese-based positive electrode material. However, since only the lithium ion diffusion coefficient is improved while the carrier mobility and electronic conductivity cannot be improved, its cycle stability cannot be improved.

[0004] In summary, most of the existing modification methods add additives during the preparation process, which are more focused on improving the rate performance and thermal stability of lithium-rich manganese-based positive electrode materials. However, how to improve the voltage and cycle stability of energy storage density of lithium-rich positive electrode materials is still a problem that needs to be solved urgently. Summary of the invention

[0005] The present invention provides a spinel / layered composite phase modified lithium-rich manganese-based positive electrode material and a preparation method thereof, so as to solve the problems of median voltage and energy storage density decay of lithium-rich manganese-based positive electrode materials in the prior art during the cycle process.

[0006] To achieve the above object, the technical solution provided by the present invention is: a method for preparing a spinel / lamella composite lithium-rich manganese-based positive electrode material with improved cycle stability, the specific steps are as follows:

[0007] Step 1: According to the general formula LiNi x Co y Mn z O2*Li2MnO3, lithium acetate, manganese acetate, cobalt acetate, and nickel acetate are added to deionized water in different molar ratios and mixed evenly, monohydrated citric acid is added as a complexing agent to complex cations to obtain a salt solution, and stirred evenly, wherein x+y+z=1, 0.5≤x<0.75, 0.2≤y<0.25, 0≤z≤0.3;

[0008] Step 2, preparing precursor powder by spray pyrolysis of the uniformly mixed solution;

[0009] Step 3, placing the precursor powder in a muffle furnace for high-temperature calcination to obtain a powder;

[0010] Step 4: Add conductive activated carbon to the powder and ball-mill in anhydrous ethanol;

[0011] Step 5: Place the ball-milled material into a blast oven for drying and allow to stand to obtain a spinel phase-modified lithium-rich manganese-based positive electrode material powder.

[0012] Furthermore, in the salt solution of step 1, the total concentration of metal ions is 0.15 mol / L, and the concentration of citric acid is 0.30-0.45 mol / L.

[0013] Furthermore, the stirring rate of the above step 1 is 400-600 r / min, and the stirring time is 1-3 hours.

[0014] Furthermore, in the above step 1, x=0.75, y=0.25, z=0.

[0015] Furthermore, the temperatures of the inlet and outlet during the spraying process in the above step 2 are set to 200-230° C. and 100-120° C. respectively, and the peristaltic speed is 10-15 rpm.

[0016] Furthermore, the high temperature calcination treatment in step three is specifically to increase the temperature by 3 degrees per minute to 1000 degrees, keep the temperature for 20 minutes, and naturally cool down to room temperature.

[0017] Furthermore, in the above step 4, the mass ratio of powder to activated carbon is 6-8:1, the ball milling rate is 400-500r / min, the mass ratio of ball milling beads to material is 100-120:1, and the time is 4-5 hours.

[0018] Furthermore, in the above step 5, the drying temperature is 60-80° C., and the drying time is 6-8 hours.

[0019] Furthermore, a spinel / layered composite phase modified lithium-rich manganese-based positive electrode material is prepared according to the above preparation method.

[0020] Compared with the prior art, the advantages of the present invention are:

[0021] 1. The present invention introduces a spinel phase into the bulk phase of the lithium-rich manganese-based positive electrode material by regulating the ratio of transition metal cations, thereby forming a spinel / layered composite phase modified lithium-rich manganese-based positive electrode material, thereby increasing the electronic conductivity of the lithium-rich manganese-based positive electrode material by about an order of magnitude, and at the same time increasing the carrier mobility, thereby greatly suppressing the decline of the median voltage and energy storage density during the cycle process.

[0022] 2. The spinel phase introduced in the present invention has a three-dimensional ion diffusion channel, which improves the transmission speed of lithium ions during the cycle, and the spinel phase has strong conductivity, which effectively improves the ionic conductivity of the material.

[0023] 3. The present invention utilizes spray hydrolysis and sintering processes to achieve spinel / layered composite phase modification by directly adjusting the ratio of transition metal cations without using additives such as alumina. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 For NCM523*Li2MnO3, NCM622*Li2MnO3, Ni 0.75 Co 0.25 *0.1C charge-discharge curves of three phase structure modifications and comparison samples of Li2MnO3;

[0025] Figure 2 The 1c 400 cycle discharge specific capacity diagram of NCM523*Li2MnO3 and the comparative example;

[0026] Figure 3 The 1c 400 cycle discharge specific capacity diagram of NCM622*Li2MnO3 and the comparative example;

[0027] Figure 4 For you 0.75 Co 0.25 *1c 400 cycle discharge specific capacity diagram of Li2MnO3 and comparative example;

[0028] Figure 5 The median voltage diagram of 1c 400 cycles of NCM523*Li2MnO3 and the comparative example;

[0029] Figure 6 The median voltage diagram of 1c 400 cycles of NCM622*Li2MnO3 and the comparative example;

[0030] Figure 7 For you 0.75 Co 0.25 *1c 400 cycle median voltage diagram of Li2MnO3 and comparative example;

[0031] Figure 8 1c 400 cycle discharge specific energy diagram of NCM523*Li2MnO3 and comparative example;

[0032] Fig. 9 The 1c 400 cycle discharge specific energy diagram of NCM622*Li2MnO3 and the comparative example;

[0033] Fig.10 For you 0.75 Co 0.25 *1c 400 cycle discharge specific energy diagram of Li2MnO3 and comparative example;

[0034] Fig.11 For NCM523*Li2MnO3, NCM622*Li2MnO3, Ni 0.75 Co 0.25 *Ionic conductivity diagrams of three phase structure modifications and comparison samples of Li2MnO3;

[0035] Fig.12 XRD refinement diagram of the comparative sample;

[0036] Fig.13 For you 0.75 Co 0.25 *XRD refinement images of three phase structure modifications of Li2MnO3;

[0037] Fig.14 For NCM523*Li2MnO3, NCM622*Li2MnO3, Ni 0.75 Co 0.25 *XRD patterns of three phase structure modifications and comparison samples of Li2MnO3;

[0038] Fig.15 For NCM523*Li2MnO3, NCM622*Li2MnO3, Ni 0.75 Co 0.25 * Raman images of three phase structure modifications and comparison samples of Li2MnO3;

[0039] Fig.16 For NCM523*Li2MnO3, NCM622*Li2MnO3, Ni 0.75 Co 0.25 *XPS images of three phase structure modifications and comparison samples of Li2MnO3;

[0040] Fig.17 These are the HADDF test results for Comparative Example 1 and Example 3. DETAILED DESCRIPTION

[0042] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0043] The chemical formula of the lithium-rich manganese-based positive electrode material prepared by the present invention is LiNi x Co y Mn z O2*Li2MnO3, x+y+z=1, 0.5≤x<0.75, 0.2≤y<0.25, 0≤z≤0.3.

[0044] Example 1: A spinel phase modified lithium-rich manganese-based positive electrode material LiNi x Co y Mn z The preparation method of O2*Li2MnO3 (x=0.5:y=0.2:z=0.3) comprises the following steps:

[0045] Step 1: Weigh acetate containing Li, Ni, Co and Mn elements according to the molar ratio shown in the chemical formula, dissolve in deionized water to prepare a mixed salt solution with a concentration of 0.15 mol / L; add citric acid as a complexing agent with a concentration of 0.3 mol / L; place the mixed solution in a magnetic stirrer, set the speed to 600 r / min, and stir for 1 hour.

[0046] Step 2: The mixed solution is granulated into a precursor by a spray dryer, with a liquid feeding rate of 10 ml / min, an air inlet temperature of 230° C., an air outlet temperature of 100-120° C., and a creeping speed of 15 rpm.

[0047] Step 3: The precursor obtained by spraying is loaded into an alumina crucible, and the temperature is raised to 1000° C. at a rate of 3° C. / min in a box furnace, kept at that temperature for 20 min, and naturally cooled to room temperature to obtain a powder.

[0048] Step 4: Mix the powder with super p powder in a ratio of 8:1, add anhydrous ethanol for wet ball milling, the mass ratio of ball milling beads to powder is 100:1, the ball milling rate is 400r / min, and the time is 4 hours.

[0049] Step 5: Place the ball-milled solution into a blast oven to dry, and allow to stand to obtain a lithium-rich manganese-based positive electrode material NCM523*Li2MnO3.

[0050] Embodiment 2: A method for preparing a spinel phase modified lithium-rich manganese-based positive electrode material NCM622*Li2MnO3, comprising the following steps:

[0051] The preparation method is basically the same as that of Example 1, except that the ratios of Ni element, Co element and Mn element added in step 1 are x=0.6, y=0.2 and z=0.2.

[0052] Example 3: A spinel phase modified lithium-rich manganese-based positive electrode material Ni 0.75 Co 0.25 * The preparation method of Li2MnO3 (x=0.75, y=0.25, z=0) comprises the following steps:

[0053] Step 1: Weigh acetate containing Li, Ni, Co, and Mn elements according to the molar ratio shown in the chemical formula, dissolve it in deionized water, and prepare a mixed salt solution with a concentration of 0.15 mol / L; add citric acid as a complexing agent with a concentration of 0.45 mol / L; place the mixed solution in a magnetic stirrer, set the speed to 400 r / min, and stir for 3 hours.

[0054] Step 2: The mixed solution is granulated into a precursor by a spray dryer, with a liquid feeding rate of 15 ml / min, an air inlet temperature of 230° C., an air outlet temperature of 100-120° C., and a creeping speed of 10 rpm.

[0055] Step 3: The precursor obtained by spraying is loaded into an alumina crucible, and the temperature is raised to 1000° C. at a rate of 3° C. / min in a box furnace, kept at that temperature for 20 min, and naturally cooled to room temperature to obtain a powder.

[0056] Step 4: Mix the prepared powder with super p powder in a ratio of 6:1, add them into anhydrous ethanol and wet ball mill them. The mass ratio of ball milling beads to powder is 120:1, the ball milling speed is 500 r / min, and the time is 5 hours.

[0057] Step 5: Place the ball-milled solution into a blast oven for drying, dry at 60°C for 8 hours, and then let stand to obtain a lithium-rich manganese-based positive electrode material Ni 0.75 Co 0.25 *Li2MnO3.

[0058] Comparative Example: Preparation of Li-rich manganese-based positive electrode material Li 1.236 Ni 0.13 Co 0.13 Mn 0.54 O2

[0059] The preparation method is the same as that of Example 3, except that the molar ratio of the reference chemical formula in step 1 is different.

[0060] The dried lithium-rich manganese-based positive electrode materials obtained in the above Examples 1-3 and the comparative example were filtered through a 300-mesh screen, and the filtered powder was mixed with the CMC aqueous solution at a mass ratio of 285:1250. Stir for 2 hours, ultrasonic for 2 hours, and stir for 2 hours. The stirred slurry was coated on aluminum foil, dried at 110°C for 20 hours, cut and dried at 115°C for 10 hours, and placed in a glove box to prepare button batteries. Tests were carried out, and the test results are as follows:

[0061] like Figure 1 As shown, at a voltage of 2-4.8V and a current of 0.1C, the first discharge specific capacities of the comparative example and embodiments 1, 2, and 3 are 291.61, 251.63, 233.73, and 246.55 mAh / g, respectively. This is because the change in the ratio of transition metal elements leads to the formation of a spinel phase, and the formation of the spinel phase reduces the discharge specific capacity.

[0062] like Figure 2 , 3, 4 and Table 2, under the same test current and voltage, the capacity cycle retention rates of the comparative example and embodiments 1, 2, 3 after 400 cycles at 1C rate are 21.48%, 80.50%, 73.07% and 72.41%, respectively. The modified samples are far superior to the original materials in terms of cycle stability. This is mainly because the spinel phase structure produced by the modification is much more stable than the original layered phase in the charge and discharge cycle, which stabilizes the material framework and inhibits harmful phase changes.

[0063] like Figure 5 , 6, 7, as shown in Table 3, the discharge median voltage retention rates of the comparative example and examples 1, 2, and 3 after 400 cycles at 1C rate are 66.57%, 79.89%, 78.38%, and 87.83%, respectively. In particular, the voltage decay of example 3 per cycle is only 1.15mV, which is much higher than 2.92mV per cycle of the comparative example.

[0064] like Figure 7 , 8, 9 and Table 4 are the discharge specific energy retention rates of the comparative example and Examples 1, 2 and 3, respectively. Thanks to the suppression of voltage decay, the discharge specific energies of the comparative example and Examples 1, 2 and 3 after 400 cycles at 1C rate are 118.30, 458.48, 404.08 and 478.65Wh / kg respectively. The specific energy retention rates are 14.93%, 68.90%, 60.66% and 63.42% respectively, which are much higher than the comparative example.

[0065] like Fig.11As shown, the EIS graphs of the comparative example, Example 1, Example 2, and Example 3, the semicircle in the high frequency region is related to the charge transfer resistance (Rct), and the oblique line in the low frequency region is the Warburg impedance, corresponding to the diffusion of lithium ions inside the electrode. The radius of the semicircle in the high frequency region of Examples 1 and 3 is smaller than that of the comparative example, and the slope in the low frequency region is also greater than that of the comparative example, because the introduced spinel phase has a three-dimensional diffusion channel for ions, which improves the migration ability of lithium ions in the lithium-rich manganese-based positive electrode material and improves its conductivity.

[0066] As shown in Table 5, the Hall effect test electronic conductivity and carriers of the comparative example, embodiment 1, embodiment 2, and embodiment 3 are shown. The comparative example, embodiment 1, embodiment 2, and embodiment 3 are all P-type semiconductors. Compared with the comparative example, the number of carriers in embodiments 1 and 2 increases, and the carrier mobility in embodiment 3 is improved.

[0067] like Fig.11 As shown, the EIS graphs of the comparative example, Example 1, Example 2, and Example 3, the semicircle in the high frequency region is related to the charge transfer resistance (Rct), and the oblique line in the low frequency region is the Warburg impedance, corresponding to the diffusion of lithium ions inside the electrode. The radius of the semicircle in the high frequency region of Examples 1 and 3 is smaller than that of the comparative example, and the slope in the low frequency region is also greater than that of the comparative example, because the introduced spinel phase has a three-dimensional diffusion channel for ions, which improves the migration ability of lithium ions in the lithium-rich manganese-based positive electrode material and improves its conductivity.

[0068] like Fig.12 , shown in Figure 13, are the XRD refinement test results of Comparative Example 1 and Example 3. In Comparative Example 1, the R-3m phase accounts for 27.51%, and the C2 / m lithium-rich phase accounts for 72.48%. In Example 3, the R-3m phase accounts for 77.36%, and the Fd-3m spinel phase accounts for 22.64%. In Example 3, the proportion of the R-3m phase increases significantly, the C2 / m lithium-rich phase disappears, and a highly conductive spinel phase is generated.

[0069] like Fig.14 As shown, the XRD test results of Comparative Example 1, Example 1, Example 2, and Example 3. Comparative Example 1, Example 1, Example 2, and Example 3 all have diffraction peaks (20-25°) of superlattice structures. As the proportion of nickel content increases, the intensity of the superstructure diffraction peak in Comparative Example 1, Example 1, Example 2, and Example 3 continues to decrease, indicating that the proportion of C2 / m lithium-rich phase decreases.

[0070] like Fig.15 Shown are the Raman test results of Comparative Example 1, Example 1, Example 2, and Example 3.

[0071] like Fig.16Shown are the XPS test results of Comparative Example 1, Example 1, Example 2, and Example 3. The peak corresponding to 531.5 eV is the surface oxygen vacancy, and the intensity of the surface oxygen vacancies in Example 1 and Example 3 is stronger.

[0072] like Fig.17 The figures show the HADDF test results of Comparative Example 1 and Example 3. In Comparative Example 1 and Example 3, the concentration distributions of three different transition metal cations, Ni, Co and Mn, are uniform.

[0073] The 0.1C charge and discharge performance of the above examples and comparative examples is listed in Table 1. The 1C discharge specific capacity cycle performance is listed in Table 2. The 1C median voltage cycle performance is listed in Table 3. The 1C discharge specific energy cycle performance is listed in Table 4. The charge transport characteristic performance is listed in Table 4.

[0074] Table 1

[0075]

[0076] Table 2

[0077]

[0078] Table 3

[0079]

[0080] Table 4

[0081]

[0082] Table 5

[0083]

[0084] In summary, embodiment 3 is the best embodiment.

[0085] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may be modified and varied in various forms. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a spinel / layered composite phase modified lithium-rich manganese-based positive electrode material, characterized in that: The specific steps are as follows: Step 1: According to the general formula LiNi x Co y Mn z O2*Li2MnO3, lithium acetate, manganese acetate, cobalt acetate, and nickel acetate are added to deionized water in different molar ratios and mixed evenly, monohydrated citric acid is added as a complexing agent to complex cations to obtain a salt solution, and stirred evenly; wherein x+y+z=1, 0.5≤x<0.75, 0.2≤y<0.25, 0≤z≤0.3; Step 2, preparing precursor powder by spray pyrolysis of the uniformly mixed solution; Step 3: placing the precursor powder in a muffle furnace for high-temperature calcination to obtain a powder; Step 4: Add conductive activated carbon to the powder and ball-mill in anhydrous ethanol; Step 5: Place the ball-milled material into a blast oven for drying and allow to stand to obtain a spinel / lamellar composite structure lithium-rich manganese-based positive electrode material powder.

2. A method for preparing a spinel / layered composite phase modified lithium-rich manganese-based positive electrode material according to claim 1, characterized in that: In the salt solution of step 1, the total concentration of metal ions is 0.15 mol / L, and the concentration of citric acid is 0.30-0.45 mol / L.

3. The method for preparing a spinel / layered composite phase modified lithium-rich manganese-based positive electrode material according to claim 1, characterized in that: The stirring rate of step 1 is 400-600 r / min, and the stirring time is 1-3 hours.

4. The method for preparing a spinel / layered composite phase modified lithium-rich manganese-based positive electrode material according to claim 1, characterized in that: In the step 1, x=0.75, y=0.25, z=0.

5. A method for preparing a spinel / layered composite phase modified lithium-rich manganese-based positive electrode material according to any one of claims 1 to 4, characterized in that: During the spraying process in step 2, the inlet and outlet temperatures are set to 200-230° C. and 100-120° C. respectively, and the peristaltic speed is 10-15 rpm.

6. A method for preparing a spinel / layered composite phase modified lithium-rich manganese-based positive electrode material according to claim 5, characterized in that: The high temperature calcination treatment in step three is specifically to increase the temperature by 3 degrees per minute to 1000 degrees, keep the temperature for 20 minutes, and naturally cool down to room temperature.

7. A method for preparing a spinel / layered composite phase modified lithium-rich manganese-based positive electrode material according to claim 6, characterized in that: In the step 4, the mass ratio of powder to activated carbon is 6-8:1, the ball milling rate is 400-500 r / min, the mass ratio of ball milling beads to material is 100-120:1, and the time is 4-5 hours.

8. A method for preparing a spinel / layered composite phase modified lithium-rich manganese-based positive electrode material according to claim 7, characterized in that: The drying temperature in step 5 is 60-80° C. and the drying time is 6-8 hours.

9. The preparation method according to claim 1 obtains a spinel / layered composite phase modified lithium-rich manganese-based positive electrode material.

Citation Information

Patent Citations

  • Layered-spinel phase composite positive electrode material and preparation method thereof

    CN111106331A

Cited By

  • Positive electrode active material for lithium secondary battery, manufacturing method therefor, and lithium secondary battery comprising same

    WO2026134922A1